The Merchant Of Venice: What Role Does Its Modern Adaptations Play? (Journal of Namibian Studies : History Politics Culture, 2023)
This paper studies on the relationship between Shylock and Jessica in Shakespeare’s The Merchant of Venice, and how this father/daughter relationship has been slightly modified on screen and in text in two important adaptations of Shakespeare’s play. These two modern adaptations of The Merchant of Venice are John Sichel’s film which was produced in 1973 and Arnold Wesker’s play The Merchant (1977). The paper argues that both adaptations tried to soften the severity of Jessica’s and Shylock’s relationship in Shakespeare’s original play. This was done by either showing direct or indirect signs of closeness between the father and his daughter. To highlight this idea, the paper will first contextualize The Merchant of Venice in order to understand why the Jewish characters were depicted in what seemed as a negative way in Shakespeare’s text, and second it will study the reasons and the methods used by both Wesker and Sichel to create more appropriate versions where the family’s ties between Shylock and Jessica are stronger. By highlighting these two aspects, the paper concludes that these interventions were not aiming to create better versions of Shakespeare’s original text, but to simply appropriate Shakespeare’s original play to the modern audience.